PENGARUH KADAR AIR TERHADAP NILAI WARNA CIE PADA GULA SEMUT - Hary Kurniawan (The University of Lampung, 2020)
Colour is one of the essential attributes as product quality criteria that determine the acceptance of a product by consumers. Granulated palm sugar is a crystalline form, which is hygroscopic. The purpose of this study was to study the colour changes through the CIELab (L, a and b) colour system to the changes in the moisture content of granulated palm sugar during storage. Changes in the values of L, a and b were observed during storage at 30oC and 76% RH. The results showed that the moisture content of granulated palm sugar increased from 3.84% wb to 8.40% wb for 10 hours of storage. The L value tends to decrease with an increasing water content which causes it to turn dark brown. While the cost of a tends to increase with increasing moisture content, the colour of the granulated palm sugar to reddish. The same thing happened to the value of b, which increases with the moisture content of granulated palm sugar and causes it tends to yellowish. Thus the change in ant sugar moisture content gives a significant difference to the L, a and b values during storage.